XBP-1s Promotes B Cell Pathogenicity in Chronic GVHD by Restraining the Activity of Regulated IRE-1α-Dependent Decay - Choi, Hee-Jin; Tang, Chih-Hang Anthony; Tian, Linlu; Wu, Yongxia; Sofi, M. Hanief; Ticer, Taylor; Schutt, Steven D.; Hu, Chih-Chi Andrew; Yu, Xue-Zhong (Frontiers in Immunology, 2021)
Allogeneic hematopoietic stem cell transplantation (allo-HCT) is an effective therapeutic procedure to treat hematological malignancies. However, the benefit of allo-HCT is limited by a major complication, chronic graft-versus-host disease (cGVHD). Since transmembrane and secretory proteins are generated and modified in the endoplasmic reticulum (ER), the ER stress response is of great importance to secretory cells including B cells. By using conditional knock-out (KO) of XBP-1, IRE-1α or both specifically on B cells, we demonstrated that the IRE-1α/XBP-1 pathway, one of the major ER stress response mediators, plays a critical role in B cell pathogenicity on the induction of cGVHD in murine models of allo-HCT. Endoribonuclease activity of IRE-1α activates XBP-1 signaling by converting unspliced XBP-1 (XBP-1u) mRNA into spliced XBP-1 (XBP-1s) mRNA but also cleaves other ER-associated mRNAs through regulated IRE-1α-dependent decay (RIDD). Besides, it is known that ablation of XBP-1s production leads to unleashed activation of RIDD. Therefore, we hypothesized that RIDD plays an important role in B cells during cGVHD development. In this study, we found that B cells deficient for XBP-1s reduced ability to induce cGVHD, which however was reversed by inactivation of IRE-1α, highlighting the role of RIDD in controlling cGVHD. Activation of RIDD targets the mRNA of IgM, a contributor to organ damage and fibrosis in cGVHD, and led to dysregulated expression of MHC II and costimulatory molecules such as CD86, CD40, and ICOSL in B cells. In conclusion, these results provide a novel insight on how ER stress response regulates B cell activity after allo-HCT and suggest RIDD is an important mediator for reducing cGVHD pathogenesis through the IRE-1α/XBP-1 pathway.